The Interface between Fungal Biofilms and Innate Immunity - Kernien, John F.; Snarr, Brendan D.; Sheppard, Donald C.; Nett, Jeniel E. (Frontiers in Immunology, 2018)
Fungal biofilms are communities of adherent cells surrounded by an extracellular matrix. These biofilms are commonly found in fungal infections, such as those caused by Candida, Aspergillus, and Cryptococcus. Clinically, biofilm infections can be extremely difficult to eradicate due to their resistance to antifungals and host defenses. Biofilm formation can protect fungal pathogens from many aspects of the innate immune system, including killing by neutrophils and monocytes. Altered immune recognition during this phase of growth is also evident by changes in the cytokine profiles of monocytes and macrophages exposed to biofilm. In this manuscript, we review the host response to fungal biofilms, focusing on how these structures are recognized by the innate immune system. We describe common themes involved in the resilience of fungal biofilms to host immunity and give examples of biofilm defenses that are pathogen-specific.